2019
DOI: 10.1177/0892705719853611
|View full text |Cite
|
Sign up to set email alerts
|

Thermal buckling and postbuckling of CNT-reinforced composite cylindrical shell surrounded by an elastic medium with tangentially restrained edges

Abstract: Buckling and postbuckling behavior of thin composite cylindrical shells reinforced by carbon nanotubes (CNTs), surrounded by elastic media and exposed to uniform temperature rise, are investigated in this article. CNTs are reinforced into isotropic matrix phase through uniform distribution or functionally graded distributions across the thickness direction. Material properties are assumed to be temperature dependent, and effective elastic moduli of CNT-reinforced composite are determined according to extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Previous investigations on FGM structures [25–29] indicated that tangential constraints of boundary edges have dramatic influences on type of buckling response and postbuckling load carrying capability of FGM plates and shells. Recent studies on FG-CNTRC structures [3039] demonstrated impressive effects of tangential edge restraints on the nonlinear stability of nanocomposite plates and shells subjected to mechanical, thermal, and thermomechanical loads. In spite of numerous investigations on FGM structures, to the best of authors’ knowledge, there is an evident lack of studies on nonlinear stability of FGM sandwich cylindrical shells with tangentially restrained edges in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on FGM structures [25–29] indicated that tangential constraints of boundary edges have dramatic influences on type of buckling response and postbuckling load carrying capability of FGM plates and shells. Recent studies on FG-CNTRC structures [3039] demonstrated impressive effects of tangential edge restraints on the nonlinear stability of nanocomposite plates and shells subjected to mechanical, thermal, and thermomechanical loads. In spite of numerous investigations on FGM structures, to the best of authors’ knowledge, there is an evident lack of studies on nonlinear stability of FGM sandwich cylindrical shells with tangentially restrained edges in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature dependency could be neglected for the thin plate. The thermal buckling responses of FG-CNTRC skew, quadrilateral, triangular, circular, sector, annular sector, elliptical plate [192,193], conical shells [194] and cylindrical shells [195,196] were also studied.…”
Section: Buckling and Postbucklingmentioning
confidence: 99%
“…Nonlinear stability of thin FG‐CNTRC CCSs under combined mechanical loads in thermal environments has been considered in work of Hieu and Tung [41] using Galerkin method. Recently, Hieu and Tung [42] analyzed the effects of tangential elasticity of edges on the buckling and post‐buckling behavior of thin FG‐CNTRC CCSs exposed to uniform temperature rise. Linear buckling analyses of FG‐CNTRC conical shells under pressure and thermal loads have been carried out in works of Kiani and coauthors [43, 44].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the combined influences of in‐plane boundary conditions and various temperature conditions on the nonlinear stability of pressure‐loaded thin FG‐CNTRC CCSs have been analyzed in work [53]. Three‐term form of the deflection and classical shell theory have been employed in the works [39, 41, 42, 52, 53] for thin shells in which transverse shear deformations are negligible. Thang et al.…”
Section: Introductionmentioning
confidence: 99%